1995
DOI: 10.1074/jbc.270.15.8928
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Is Conjugated to the Cytoskeletal Protein α-Spectrin in Mature Erythrocytes

Abstract: Ubiquitination of red blood cell (RBC) proteins was investigated by encapsulation of 125I-ubiquitin into human erythrocytes using a procedure of hypotonic dialysis, isotonic resealing, and reannealing. Incubation (37 degrees C, up to 2 h) of 125I-ubiquitin-loaded cells resulted in the recovery of 125I-ubiquitin with the cytosolic proteins (9.22 +/- 0.4 micrograms/ml RBC) and conjugated to membrane proteins (2.18 +/- 0.05 micrograms/ml RBC). This conjugation was time-dependent, and the predominant membrane prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Peptide mapping and Edman degradation analysis showed that biotins were at Lys 6 , Lys 48 , and Lys 63 in tribiotinylated ubiquitin (Table I). Taken together, these data indicate that the order of susceptibility of amino groups in ubiquitin to modification by sulfo-NHS-biotin is Lys 6 Ͼ Ͼ Lys 63 Ͼ Lys 48 Ͼ Ͼ Lys 33 Ͼ Ͼ Lys 11 , Lys 27 , and Lys 29 .…”
Section: Lys 6 Of Ubiquitin Is the Most Readily Labeled With Sulfo-nhmentioning
confidence: 74%
See 1 more Smart Citation
“…Peptide mapping and Edman degradation analysis showed that biotins were at Lys 6 , Lys 48 , and Lys 63 in tribiotinylated ubiquitin (Table I). Taken together, these data indicate that the order of susceptibility of amino groups in ubiquitin to modification by sulfo-NHS-biotin is Lys 6 Ͼ Ͼ Lys 63 Ͼ Lys 48 Ͼ Ͼ Lys 33 Ͼ Ͼ Lys 11 , Lys 27 , and Lys 29 .…”
Section: Lys 6 Of Ubiquitin Is the Most Readily Labeled With Sulfo-nhmentioning
confidence: 74%
“…Biotinylated ubiquitin has been used as a probe to study the function of the UPP (27). However, biotinylated ubiquitin has not been characterized in detail, and the potential kinetic artifacts of biotinylated ubiquitin have not been assessed.…”
mentioning
confidence: 99%
“…It is possible that the association of ␣-and ␤-Spectrin blocks ubiquitination of ␣-Spectrin and its subsequent degradation via the proteasome. Ubiquitination has been previously reported for ␣-Spectrin (Corsi et al, 1995;Galluzzi et al, 2001) and may thus help to define the correct protein-expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations suggest that fodrin, an analog of spectrin, which is a major component of the cortical cytoskeleton of most eukaryotic cells, is degraded during apoptosis in a variety of cells, including T-lymphoma cells [19]. Moreover, it is known that c~-spectrin can be ubiquitinated [20], and that cells deficient in spectrin tend to show a blebbing reminiscent of the morphology of apoptotic cells [21]. In addition, partial degradation of actin during apoptosis was observed recently in human leukemia U93H cells [22].…”
Section: F Pitzer Et Al/febs Letters 394 (1996) 47 50mentioning
confidence: 99%